2011
DOI: 10.1002/ptr.3414
|View full text |Cite
|
Sign up to set email alerts
|

Asperosaponin VI, A Saponin Component from Dipsacus asper Wall, induces Osteoblast Differentiation through Bone Morphogenetic Protein‐2/p38 and Extracellular Signal‐regulated Kinase 1/2 Pathway

Abstract: Osteoporosis is a reduction in skeletal mass because of the loss of osteoblastic activity or an increase in osteoclastic activity. The survival of osteoblast cells plays a crucial role in the development of osteoporosis. Asperosaponin VI (ASA VI) is a kind of saponin in the medicinal herb Dipsacus asper Wall which has long been used as an antiosteoporosis drug. The assay of cell proliferation, alkaline phosphatase (ALP) activity and measurement of mineralized matrix, showed that ASA VI exhibited a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 29 publications
(38 reference statements)
3
42
0
Order By: Relevance
“…These compounds can be divided into 6 categories, including flavonoids: icariin (Figure 1) [2326], genistein (Figure 2) [29], daidzein (Figure 2) [31, 32], kaempferol (Figure 11) [72], quercetin (Figure 11) [73, 74], naringin (Figure 8) [75–77], hesperidin (Figure 11) [78], linarin (Figure 11) [79], bavachalcone (Figure 3) [36], rutin (Figure 11) [80], (+)-catechin (Figure 11) [81], nobiletin (Figure 11) [82], luteolin (Figure 11) [83], baicalein (Figure 11) [84], baicalin (Figure 1) [85], xanthohumol (Figure 11) [86]; coumarins: psoralen (Figure 3) [35], osthole (Figure 11) [87]; lignans: honokiol (Figure 11) [88, 89], isotaxiresinol (Figure 11) [90], magnolol (Figure 11) [91]; polyphenol: resveratrol (Figure 11) [9295], curcumin (Figure 11) [9698], tea polyphenols (including epigallocatechin-3-gallate, epigallocatechin, epi-catechin, epicatechin-3-gallate, Figure 11) [99, 100]; anthraquinones: rubiadin (Figure 10), 2-hydroxy-1-methoxy-anthraquinone (Figure 10), 1,3,8-trihydroxy-2-methoxy-anthraquinone (Figure 10) [71]; alkaloids: harmine (Figure 11) [101], coptisine (Figure 11) [102], palmatine (Figure 11) [103], berberine (Figure 11) [104, 105]; and other compounds: curculigoside (Figure 11) [106, 107], asperosaponin VI (Figure 11) [108], limonoid 7-oxo-deacetoxygeduni...…”
Section: Resultsmentioning
confidence: 99%
“…These compounds can be divided into 6 categories, including flavonoids: icariin (Figure 1) [2326], genistein (Figure 2) [29], daidzein (Figure 2) [31, 32], kaempferol (Figure 11) [72], quercetin (Figure 11) [73, 74], naringin (Figure 8) [75–77], hesperidin (Figure 11) [78], linarin (Figure 11) [79], bavachalcone (Figure 3) [36], rutin (Figure 11) [80], (+)-catechin (Figure 11) [81], nobiletin (Figure 11) [82], luteolin (Figure 11) [83], baicalein (Figure 11) [84], baicalin (Figure 1) [85], xanthohumol (Figure 11) [86]; coumarins: psoralen (Figure 3) [35], osthole (Figure 11) [87]; lignans: honokiol (Figure 11) [88, 89], isotaxiresinol (Figure 11) [90], magnolol (Figure 11) [91]; polyphenol: resveratrol (Figure 11) [9295], curcumin (Figure 11) [9698], tea polyphenols (including epigallocatechin-3-gallate, epigallocatechin, epi-catechin, epicatechin-3-gallate, Figure 11) [99, 100]; anthraquinones: rubiadin (Figure 10), 2-hydroxy-1-methoxy-anthraquinone (Figure 10), 1,3,8-trihydroxy-2-methoxy-anthraquinone (Figure 10) [71]; alkaloids: harmine (Figure 11) [101], coptisine (Figure 11) [102], palmatine (Figure 11) [103], berberine (Figure 11) [104, 105]; and other compounds: curculigoside (Figure 11) [106, 107], asperosaponin VI (Figure 11) [108], limonoid 7-oxo-deacetoxygeduni...…”
Section: Resultsmentioning
confidence: 99%
“…The membranes were washed three times for 10 min with TBS buffer, and once for 10 min with PBS. Detection was performed using the enhanced chemiluminescence western blotting detection system (Millipore, MA, USA) (34).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the Chinese teasel root promotes the proliferation and differentiation of osteoblasts, and is able to regulate immune function, indicating that it may be used to treat arthritis (12). A kind of saponin in the medicinal herb Dipsacus asper wall has been used as an antiosteoporosis drug (13). However, its therapeutic mechanism of action remains unclear and further studies are required to screen and separate active components.…”
Section: Introductionmentioning
confidence: 99%